Online Marriage During the Covid-19 Pandemic: A Study of the Fatwas in Egypt, Iraq, Syria, and Saudi Arabia - Hakim, Abdul; Qodsiyah, Bagus Haziratul (Universitas Islam Negeri Raden Intan Lampung, 2022)
Online Marriage During the COVID-19 Pandemic: A Study of the Fatwas in Egypt, Iraq, Syria, and Saudi Arabia. Online marriage is a new social phenomenon that has emerged since the arrival of the COVID-19 virus outbreak in all corners of the world. This phenomenon is widely discussed by people everywhere and is motivated by the desire to carry out pre-planned marriages and not wanting to postpone them. This study aims to discuss the above social phenomena from the point of view of fiqh, maqāshid al-sharīa, and fatwas in several Muslim countries. This type of research is qualitative in the form of a literature study using a conceptual and socio-legal approach. Based on the results of the study, it can be concluded that the views of fiqh and fatwas in Muslim countries regarding online marriage are divided into two: Some allow it because they regard virtual meetings as meetings in one place (ittihād al-majlis) and consent and qabūl can be witnessed by both witnesses; but some forbid it because there is no physical and essential ittihād al-majlis, there are no witnesses, and the possibility of audio-visual manipulation. Viewed from the maqāshid al-sharīa perspective, online marriage is also not suitable because the purpose of marriage may not be realized.